The impact of school climate on academic burnout of Chinese students: the mediating effect of psychological capital - Tang, Xiao-ling (Frontiers in Education, 2024)
Background: Students are in their teenage years during middle school, which is a period of acceleration and transition for individual physical and mental development. Therefore, junior high school students are easily influenced by their internal and external environment, leading to academic burnout. The main activity venue for middle school students in school homework is the external environment that affects their academic performance. Psychological capital is the student's own resource and the external environment that affects their academic performance. Aims: This study aims to explore the interrelationship among school atmosphere, psychological capital, and academic burnout, and construct a theoretical model among them. This study provides practical and feasible methods and guidance suggestions for educational institutions and teachers, helps students improve their mental health level, enhances the positive perception level of the school atmosphere, and alleviates their academic burnout. Methods: Building upon previous research on school climate, psychological capital, and academic burnout, this study employed the following research tools: The Perceived School Climate Questionnaire (PSC), the Positive Psychological Questionnaire (PPQ), and the High School Students' Academic burnout Scale. A questionnaire survey was conducted on 1,267 students from three different regions of Chongqing, involving various types of junior high schools.The findings of this study demonstrate that both the external school climate and internal psychological capital exert an impact on academic burnout. A positive school climate can foster the development of psychological capital, subsequently enhancing academic performance. Additionally, psychological capital directly influences academic burnout. The higher the level of positivity is, the more pronounced the alleviating effect becomes. The school climate can directly affect academic burnout, and it can also indirectly affect academic burnout through the mediation of psychological capital, with psychological capital playing a partial mediating role. Conclusions: To avoid academic burnout, schools should actively create a good school atmosphere and mobilize students' learning enthusiasm; Teachers should provide targeted psychological counseling to reduce students' negative emotional perception; Students should correct their learning attitude and recognize their own learning status.